Pengembangan E-Modul Meporis Berbasis Android untuk Pembelajaran Pola Organis dan Geometris - Widari, Maeyrena Ika; Prasetyo, Abdul Rahman (Jurnal Pendidikan dan Penciptaan Seni, 2025)
This research produces learning media in the form of e-modules based on Android applications which are effective in increasing students' understanding of organic and geometric pattern material. The trial results showed that the material validity test reached 75% and the media validity test reached 85%, the effectiveness score was 90% with an increase in learning outcomes based on the N-Gain value of 64%, so this e-module is suitable for implementation in schools. The research model used is 4D, including four stages: Define (define), Design (design), develop (development), and disseminate (dissemination). Data was obtained through observation, interviews, document studies, expert validation, and product trials. The completeness analysis revealed that conventional learning media was less interesting causing low student learning outcomes, so media was needed that utilized interactive technology. The Android application-based e-module was chosen because it suits current developments and students' preferences, allows them to learn independently flexibly and understand the material well. This research aims to describe needs analysis, develop learning media, and test the effectiveness of the media.